Development of a green drink with spirulina (Arthrospira sp.) using the experimental mixture design - Bolaños-Quirós, Fiorella (2024)
Introduction. There is a tendency to consume spirulina (Arthrospira sp.) due to its nutritional value and potential as a sustainable protein source. Spirulina has an intense flavor and odor that can be disliked by consumers, so it is convenient to use the experimental design of mixtures to optimize the formulation. Objective. To develop a prototype of a green beverage prototype with high nutritional value that incorporates spirulina as an ingredient, through the application of an experimental mixture design. Materials and methods. The research was carried out at Universidad de Costa Rica, Liberia campus, in Guanacaste, between July and December 2022. Eleven prototypes of a spirulina-based beverage were prepared, and a space-filling mixture design was applied with three factors (spirulina, sugar, and fruits/vegetables) and overall acceptability as the response variable. Acceptability was evaluated by a panel of 95 consumers, with the averages adjusted using the Scheffe polynomial model. The model equation was obtained using JMP16 software and validated by a panel of 27 consumers with five samples. Physicochemical analyses were conducted to determine the nutritional value of a selected beverage prototype. Results. The factors were found to influence product acceptability (p<0.05). The values of R2=0.97 and adjusted R2 -adj=0.96 indicated that the model fits the experimental data. Validation confirmed that the model reliably predicts overall acceptability. The formulation, which contains 2 % spirulina and a 300 mL serving, was characterized as low in sodium, a source of protein and magnesium, and rich in iron and vitamin C. Conclusions. It was possible to obtain a significant and adjusted mathematical model that manages to predict the liking of a beverage with spirulina. The developed prototype contains more spirulina and protein than similar beverages on the market.